The role of seagrass meadows as Blue Carbon ecosystems and nutrient and pollutant traps: supporting factors and threats - CAVIGLIA, Laura (Università degli Studi di Palermo, 2024)
Seagrass meadows are aquatic angiosperms that are common in estuaries and coastal waters of all continents except Antarctica and provide various ecosystem services, including the promotion of biodiversity and fisheries, coastal protection, support for tourism, recreation, education and research. These underwater habitats are also referred to as Blue Carbon ecosystems, as they act as carbon sinks, storing organic carbon from senescent seagrass biomass and allochtnonous organic matter in their underlying sediment, for centuries to millennia. Additionally, seagrass meadows function as filtering habitats, particularly for nutrients like nitrogen, thereby playing a crucial role in the mitigation of water eutrophication. Furthermore, recent studies suggested that seagrasses act as a filter for pollutants of emerging interest (microplastics). The storage of carbon, nutrients and pollutants in seagrass sediments appears to be very heterogeneous, even when considering the same species. For this reason, recent studies have focused on the interaction between the characteristics of seagrasses and the environmental factors that may influence their storage and filtering capacity. Nevertheless, knowledge gaps persist regarding the factors that influence seagrass storage capacity of carbon and nutrients as well as their role as traps for microplastics. Unfortunately, seagrass meadows are being lost globally, due to diverse anthropogenic factors like habitat destruction, pollution, non-native species introduction and climate change. The loss of seagrass meadows exposes sediments to remineralization and physical disturbance, potentially leading to the release of stored carbon, nutrients and pollutants. For this reason, marine habitat restoration has become a pivotal management strategy to counter seagrass ecosystems decline and enhance resilience. However, effective monitoring programs and knowledge of the areas subjected to restoration are essential to evaluate the outcomes of these projects. This study aims to advance our ...